The Effect of Management, Motivation, and Discipline Implementation on Employee Job Satisfaction: A Survey at The Indonesian Public Health Center - Kosasih; Detya Okti Murni; Ayu Laili Rahmiyati; Etty Sofia Mariati Asnar; Farida Yuliaty (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Health services provided by community health center employees can run optimally if they are supported by good management, employee work motivation, job satisfaction, and high discipline so that they can improve employee performance. This type of research is quantitative and has a descriptive analysis approach. The sample was 48 Community Health Center employees obtained using a total sampling technique. Data was collected by questionnaire and then analyzed by multiple linear regression using SPSS 25.0 software. The research results showed that the implementation of BLUD (The Regional Public Service Agency) service management, work motivation, work discipline and job satisfaction were in the high category. The results of statistical tests obtained the BLUD management service variable with a coefficient of 0.368 and ap value of 0.000, motivation with a coefficient of 0.395 and ap value of 0.001, and work discipline with a coefficient of 0.007 and ap value of 0.007, so it can be concluded that these three variables have an influence on job satisfaction. The BLUD management variables, motivation and discipline together influence employee job satisfaction at the Sukahening Tasikmalaya Community Health Center with ap value of 0.000.